Răspuns :
-9+(-8)+(-7)+(-6)+(-5)+(-4)+(-3)+(-2)+(-1)+0+1+2+3+4+5+6+7+8+9
=-9-8-7-6-5-4-3-2-1+1+2+3+4+5+6+7+8+9
=0
Se obsevă că toți termenii se reduc :
-9 cu 9,-8 cu 8,etc.
Cred că te refereai la suma numerelor întregi.
=-9-8-7-6-5-4-3-2-1+1+2+3+4+5+6+7+8+9
=0
Se obsevă că toți termenii se reduc :
-9 cu 9,-8 cu 8,etc.
Cred că te refereai la suma numerelor întregi.
(-9)+(-8)+(-7)+(-6)+(-5)+(-4)+(-3)+(-2)+(-1)+0+1+2+3+4+5+6+7+8+9=
(-17)+(-13)+(-9)+(-5)+(-1)+45=
(-30)+(-15)+45=
(-45)+45=0
(-17)+(-13)+(-9)+(-5)+(-1)+45=
(-30)+(-15)+45=
(-45)+45=0